Corrosion protection of AA6061-T4 alloy by sol-gel derived micro and nano-scale hydroxyapatite (HA) coating - Sonmez, S.; Aksakal, B.; Dikici, B. (SPRINGER, 2012)
Micron and nano-scale hydroxyapatite (HA) were coated successfully on AA6061-T4 substrates by sol-gel method. Besides, the effects of coating thickness on adhesion strength and corrosion behaviour of the coatings were studied. Corrosion resistance was measured by potentiodynamic polarization test using a potentiostat under in vitro conditions. The coatings before and after corrosion tests were characterized by adhesion tests, a scanning electron microscopy attached with EDS and X-ray diffraction analysis. The results revealed that all the coatings exhibit a passive behaviour in Ringer's solution. Specimens coated with nano-scale HA had the higher corrosion resistance than micro-scale coatings. The highest corrosion resistance appeared to be for the similar to 30 mu m nano-scale HA coated substrates. However, for micro-scale HA coatings, the highest adhesion resistance was obtained at similar to 30 mu m film thickness.
Keywords: Hydroxyapatite; A6061-T4; Sol-gel; Corrosion; MECHANICAL-PROPERTIES; TITANIUM; RESISTANCE; GROWTH; Materials Science